Computationally Efficient Assessments of the Effects of Radiative Transfer, Turbulence Radiation Interactions, and Finite Rate Chemistry in the Mach 20 Reentry F Flight Vehicle. (9th June 2016) - Krishnamoorthy, Gautham; Clarke, Lauren Elizabeth
Abstract : Effects of finite rate chemistry, radiative heat transfer, and turbulence radiation interactions (TRI) are assessed in a fully coupled manner in simulations of the Mach 20 Reentry F flight vehicle. Add-on functions were employed to compute a Planck mean absorption coefficient and the temperature self-correlation term (for TRI effects) in the optically thin shock layer. Transition onset was induced by specifying a wall roughness height at the experimentally observed transition location. The chemistry was modeled employing eight elementary reactions and an equilibrium approach allowing species to relax towards their chemical equilibrium values over the process characteristic time scale. The wall heat fluxes in the turbulent region, density, and velocity profiles compared reasonably well against measurements as well as similar calculations reported previously. The density predictions were more sensitive to the choice of modeling options than the velocities. The radiative source term magnitude agreed closely with its measurements deduced from shock tube experiments. The TRI model predicted a 60% enhancement in emission due to temperature fluctuations in the turbulent boundary layer. While the variations in density and velocity predictions among the models diminished along the length of the body, the O and NO prediction variations extended well into the turbulent boundary layer.